Indeterminate cell tumor (Histiocytosis) - Ayesha Ahmed; Mohamed A Shawarby; Dalal M Al-Tamimi; Zainab A Al-Ruwai; Tarek M El-Sharkawy; Tarek M Hashem; Eman F Al-Saleh (Saudi Journal of Medicine and Medical Sciences, 2013)
Indeterminate cell tumor (ICT; histiocytosis) is a rare disorder characterized by accumulation of histiocytes that do not fulfill the phenotypic criteria designated for Langerhans cells (LC). The cells classified as "indeterminate" exhibit overlapping features between dendritic cells and histiocytic cells by showing variable reactivity for CD1a and positivity for S-100 protein and CD68. Ultrastructurally, absence of Birbeck granules, a feature consistent with LC, epitomizes the lesional cells. Herein, we report a case of ICT in a new born emphasizing its histogenesis and clinical, morphologic, immunohistochemical, and ultrastructural features.